A Participatory Co‑creation Model to Drive Community Engagement in Rural Indigenous Schools: A Case Study in Sarawak - Jacey Lynn, Minoi; Fitri Suraya, Mohamad; Sylvester, Arnab; Phoa, John; Morini, Luca; Beaufoy, Jayne; Lim, Terrin; Clarke, Samantha (Academic Conferences and Publishing International Limited, 2019)
This paper presents the formulated ‘play‑to‑engage’ model for indigenous community engagement that incorporates factors in cultural protocols and game design thinking. The hybrid model of the participatory co‑creation model was formulated in the study that had been rolled out in two rural primary schools in West Borneo. These schools are located in remote villages, away from urban amenities, and technological affordances and resources are limited. There are more than twenty culturally‑diversed indigenous tribes in Borneo. Although it is a known fact that indigenous cultures, including those in Borneo, have many cultural protocols and distinctive custom practices, it is still a challenge for researchers who work with such communities to understand, adhere to and follow the cultural protocols. The model looks at incorporating gameplay and culture protocols to drive community engagement. Since play is universal, the creation of a trustworthy partnership between the community and researchers was established through the use of play during the engagement process. Narratives captured in the study represented reflection, problem solving and creativity in the interactions with the indigenous communities, based on the developed indicators of the ‘play‑to‑engage’ model.